Influence of Nb doping on magnetic properties of nanocrystalline Nd-Fe-B alloys - Bilovol, Vitaliy (2013)
The influence of Nb doping was studied on ribbons of nominal composition NdyFe86-x-yB14Nbx (y = 7, 8; x = 0, 2, 4). The alloys were prepared by melt-spinning and then annealed at 973 K for 20 minutes. The magnetic characterization revealed that niobium addition improves substantially the magnetic properties of the studied alloys. The structural characterization showed that, in most alloys, the magnetically hard phase Nd2Fe14B precipitated as the main phase. This was not the case for the ternaries (x = 0) and for the Nd7Fe77B14Nb2 alloys. Furthermore, the addition of Nb inhibited the precipitation of α-Fe, independently of the Nd content. From the complete set of samples studied in this work, we found that the sample with nominal composition Nd8Fe74B14Nb4 exhibited the highest coercive field HC = 575 kA/m while Nd7Fe75B14Nb4 showed the highest maximum energy product, (BH)max = 73 kJ/m3.